Pharmacological inhibition of EZH2 disrupts the female germline epigenome - Prokopuk, Lexie (Clin Epigenetics, 2018)
BACKGROUND: Recently discovered drugs that target epigenetic modifying complexes are providing new treatment options for a range of cancers that affect patients of reproductive age. Although these drugs provide new therapies, it is likely that they will also affect epigenetic programming in sperm and oocytes. A promising target is Enhancer of Zeste 2 (EZH2), which establishes the essential epigenetic modification, H3K27me3, during development. RESULTS: In this study, we demonstrate that inhibition of EZH1/2 with the clinically relevant drug, tazemetostat, severely depletes H3K27me3 in growing oocytes of adult female mice. Moreover, EZH2 inhibition depleted H3K27me3 in primary oocytes and in fetal oocytes undergoing epigenetic reprogramming. Surprisingly, once depleted, H3K27me3 failed to recover in growing oocytes or in fetal oocytes. CONCLUSION: Together, these data demonstrate that drugs targeting EZH2 significantly affect the germline epigenome and, based on genetic models with oocyte-specific loss of EZH2 function, are likely to affect outcomes in offspring. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13148-018-0465-4) contains supplementary material, which is available to authorized users.